The Integration of Women’s Roles and Innovation Capability on Women’s Creativity with Work – Family Balance as a Moderating Variable: A Study of Micro – Scale Food Vendors in Cirebon Regency - Laely Kholifah; Anna Suzana (Interdisciplinary Social Studies, 2026)
While female entrepreneurs in Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in economic development, they frequently face challenges in balancing dual responsibilities between work and family. These conditions require effective role integration, innovation capability, and work–family balance to enable female MSME entrepreneurs to sustain and enhance their creativity in managing their businesses. Therefore, this study aimed to examine the influence of women’s role integration and innovation capability on the creativity of female MSME entrepreneurs in Cirebon Regency, while also investigating the role of work–family balance as a moderating variable. This study employed a quantitative approach, with data collected through questionnaires. The sample consisted of 130 female entrepreneurs operating micro-scale food businesses in Cirebon Regency. Data were analyzed using regression analysis with the assistance of SPSS version 29. The findings showed that women’s role integration and innovation capability had positive and significant effects on the creativity of female MSME entrepreneurs. However, the moderation analysis revealed that work–family balance did not moderate the relationship between role integration or innovation capability and women-led MSME creativity. This study demonstrated that women’s ability to effectively manage multiple roles and strengthen their innovation capability significantly enhanced creativity in MSME management. By highlighting the importance of individual capabilities and human capital over contextual factors in fostering innovation among women-led MSMEs, this study contributes to the existing literature on women entrepreneurship and business creativity.